The impact of temperature trends from years 2000-2015 on regional economic growth in the Philippines using panel data estimation - Luzon, Grace D. (Animo Repository, 2018)
This study uses historical fluctuations of temperature and other weather - related variables to measure the impact of weather on the gross value added of the agricultural sector. It covers the period of 16 years, from 2000 to 2015. Using both simple and sophisticated estimation frameworks for panel data, the study finds that the labor productivity, gross fixed capital formation on durable equipment in the agricultural sector, and average rainfall are statistically significant predictors of gross value added. Using a panel generalized methods of moments (GMM) estimator, the study also finds empirical support for average rainfall as an important determinant of gross value added in agriculture.